GEOPOLITICS IN THE INFRASTRUCTURAL IDEOLOGIES OF 5G - Dunajcsik, Peter 'Maxigas'; ten Oever, Niels (AoIR Selected Papers of Internet Research, 2021)
This paper explores how infrastructural ideologies function as tools in geopolitical struggles for dependence and independence of world powers. Meese Frith and Wilken (2020) suggest that controversies around 5G stem from infrastructural anxieties best examined in the framework of geopolitics. We build on this work by analyzing the emerging infrastructural imaginary of 5G in light of the changing global division of labor. Sociotechnical imaginaries (Jasanoff and Kim 2015) refer to the vision of technologies themselves, while ideologies refer to the totality of social relations, translating the objective reality of material conditions to subjective lived experience (Bory 2020). The Western imaginaries around 5G infrastructures reflect, deflect, translate and sublimate the infrastructural anxieties tied to the development and deployment of new network paradigms. Their controversial nature, contradictory content, and fragmented presentation is a necessary part of living through the trauma of lost historical agency on the part of Western superpowers. We engaged in code ethnography (Rosa 2019) of GSM, internet, and 5G technologies, as well as participant observation in the main standard-development organizations of the internet and 5G, and semi-structured interviews with equipment vendors and network operators. Our methodological assumption, taken from World Systems Theory (Wallerstein and Wallerstein 2004), is that the character and content of imaginaries and their underpinning ideologies creatively reflect the position of actors in the global division of labor. This paper contributes to the understanding of the role of infrastructures in geopolitical power tussles and straddles the fields of science and technology studies and international relations.